Konsentrasi Hambat Minimum dan Konsentrasi Bunuh Minimum Ekstrak dan Nanopartikel Ekstrak Etanol Daun Kubis (Brassica oleracea L.) Terhadap Malassezia furfur - Rafika, Intan Maya; Rahayu , Yayuk Putri; Nasution , Haris Munandar; Miswanda, Dikki (Journal of Pharmaceutical and Sciences, 2025)
Background: Dandruff is a condition characterized by excessive shedding of dead skin cells on the scalp, often accompanied by itching and inflammation. The causes of dandruff can be related to excessive secretion of sweat glands or the presence of microorganisms on the scalp that produce specific metabolites that trigger dandruff formation. The organism believed to be the leading cause of dandruff is Malassezia furfur. Treatment for dandruff can be done through various methods, one of which is using natural extracts, such as ethanol cabbage extract, known for its antifungal properties. In this study, the ethanol cabbage extract will be synthesized into nanoparticle form to enhance its effectiveness. Objective: The objective of this study is to create nanoparticles from ethanol cabbage extract and to compare the antifungal activity of the cabbage extract and the nanoparticle extract of cabbage against Malassezia furfur, focusing on the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). Method: This study was conducted experimentally, and two variables were tested. The independent variables included the concentration of cabbage extract (6.25%, 12.5%, 25%, and 50%) and nanoparticle cabbage extract (0.625%, 1.25%, 2.5%, and 5%). The dependent variables were the antifungal activity measured by MIC and MFC tests against Malassezia furfur. Nanoparticles were synthesized using the top-down method with high-speed homogenization (HSH) technique. The particle size characterization was performed using a Particle Size Analyzer (PSA). Results: Particle size characterization showed that the particle size of cabbage extract was 2203.45 nm, while the nanoparticle size after synthesis was 408.33 nm. Based on the MIC and MFC tests, it was found that the nanoparticle ethanol cabbage extract at a concentration of 1.25% was more effective than the ethanol cabbage extract at 12.5%. Additionally, the MFC value of the nanoparticle ethanol cabbage extract at a concentration of 5% was more effective than that of the ethanol cabbage extract at 50%. Both preparations demonstrated good sensitivity against Malassezia furfur. Conclusion: Nanoparticle ethanol cabbage extract showed better antifungal activity than the ethanol cabbage extract at higher concentrations. These results indicate that using nanoparticles can reduce the required dosage to achieve optimal effectiveness, thus improving the efficiency of the drug in dandruff treatment.